Місце біометричного паспорта в системі документів, що підтверджують громадянство України - Безсонна, Т. Ф.; Bezsonna, T. F.; ORCID: http://orcid.org/0000-0002-2482-9564 (Вісник Луганського держаного університету внутрішніх справ імені Е. О. Дідоренка. – 2017. – № 3 (79). – С. 132-138, 2017)
На підставі аналізу наукової літератури та нормативно правових актів проаналізовано систему документів, які підтверджують громадянство України. Визначено місце біометричного паспорта в системі документів, що підтверджують громадянство. Проаналізовано особливості біометричного паспорта. З’ясовано значення вказаного документа для попередження злочинів.

On the basis of analysis of scientific literature and normative legal acts, the system of documents and confirming the citizenship of Ukraine are analyzed. The main documents confirming the citizenship of Ukraine are: 1) the passport of a citizen of Ukraine; 2) a passport of a citizen of Ukraine for traveling abroad; 3) temporary proof of a citizen of Ukraine; 4) a diplomatic passport; 5) official passport; 6) certificate of the identity of the seaman; 7) certificate of crew member; 8) Identity card for returning to Ukraine. The passport system plays an important role in realizing the rights and obligations of citizens with the help of the introduced documentation, which certifies the identity of the established model. Early in the essence of the passport system, the state regulates the registration of citizens not only according to place of residence, but also at the place of their temporary stay. Thanks to the passport system, public order protection and public security are provided. The passport system plays a role in combating crime, tracing criminals and preventing offenses. Passport system in a combined mailing, where you can go to the street, to inspect the territory of this or that state. This must be done to cross and prevent crime. The place of the biometric passport in the system document, confirming the citizenship is determined. One of them is that it can be used as an intermediary and can not be used to obtain information about it. The features of the biometric passport are analyzed. The modern biometric passport of a citizen of Ukraine makes it possible to identify a person not only in photography but also in biometrics and has a high level of protection. Defined in documentary document for crime prevention. Documents that contain contactless electronic media are considered to be most protected against forgery and allow anyone other than the owner to use.

На основании анализа научной литературы и нормативно-правовых актов проанализирована система документов, подтверждающих гражданство Украины. Определено место биометрического паспорта в системе документов, подтверждающих гражданство. Проанализированы особенности биометрического паспорта. Определено значение указанного документа для предупреждения преступлений.
Безсонна, Т. Ф. Місце біометричного паспорта в системі документів, що підтверджують громадянство України / Т. Ф. Безсонна // Вісник Луганського держаного університету внутрішніх справ імені Е. О. Дідоренка. – 2017. – № 3 (79). – С. 132-138.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; паспортна система; паспортная система; passport system; паспорт; паспорт громадянина України для виїзду за кордон; біометричні дані; біометричний паспорт; документи, що засвідчують особу; паспорт гражданина Украины для выезда за границу; биометрические данные; биометрический паспорт; документы, удостоверяющие личность; passport system; passport; passport of a citizen of Ukraine for traveling a broad; biometric data; biometric passport; which certify a special security person